Multifunctional land use in the Amsterdam South Axis area - a cost-benefit analysis - Paul Besseling; Jos Ebregt; Rafael Saitua; Ioulia Ossokina (European Regional Science Association (ERSA), 2005)
The Amsterdam South Axis area is situated along one of the country's major transport corridors and in the vicinity of both the Schiphol airport and the cultural centre of Amsterdam. Therefore it is usually seen as a prime location for offices of domestic and foreign companies. This paper uses the technique of global cost-benefit analysis to assess the welfare effects of an investment project involving a new business district and living quarter in the South Axis. Two project alternatives are considered that combine urban construction and infrastructural investment. The most ambitious of the two creates extra room for construction by bringing all rail and road infrastructure underground. This study distinguishes three direct effects of the South Axis project: on the land market, on the transport market and external effects. Furthermore, an indirect effect on the employment is taken into account. As the aim of the global cost-benefit analysis is to give a first impression of the costs and benefits of a project the first two direct effects are quantified, the other effects are assessed qualitatively. This paper suggests that neither of the two project alternatives has a positive balance of benefits and costs in comparison to the (little ambitious) reference scenario. The last was defined to involve realisation of the construction plans decided upon by the time the study started. In both project alternatives the largest part of the benefits is obtained from the issue of land for construction purposes. This land is very valuable due to the unique location of the area. However, the land benefits together with the (rather small) transport benefits turn out to be modest in comparison with the considerable costs involved in modifying the transport infrastructure. Other effects of the project are expected to be of such size that they do not affect the direction of the above results. The analysis concludes by making some suggestions as to how the alternatives may be adjusted as to achieve a positive balance of costs and benefits that may be expected on basis of the unique location of the South Axis key-site.
Keywords: 330